Ascidian diversity of Costa Rica, including new records for the North Pacific - González Sánchez, Kaylen (2021)
Introduction: The class Ascidiacea has about 3 000 species, which fulfill various roles in the ecosystem, for example, they filter high amounts of particles, and are shelter and food for other animals. Furthermore, the group has a high number of invasive species reported. In Costa Rica, ascidians have been barely studied. Objective: In this study, we aim to describe the diversity of ascidians in Costa Rica from new samplings in Área de Conservación Guanacaste, North Pacific, and by compiling previous reports for the entire country in order to improve the group’s state of knowledge. Methods: Samples were collected during two field trips between 2018 and 2019, at six sites within the Gulf of Santa Elena and three sites near the Murcielago Islands area. The specimens were dissected and analyzed in detail to determine the species. All the identifications were compared with the available information from literature and from museum collections. Literature, collections databases of the National Museum of Natural History, Smithsonian Institution and the new material collected were used to create an updated taxonomic list. Results: A total of eight species were obtained from 70 specimens. Of these, five are new reports for the country, which increase to 22 species the total number reported for Costa Rica. The most common species was Rhopalaea birkelandi, whose presence was higher in Santa Elena Bay. Conclusions: This study improved the knowledge of ascidian diversity in Costa Rica. Polyandrocarpa anguinea, reported for the first time, is considered invasive in other areas, which suggests the necessity of a continuous monitoring of its population. It is necessary to include more areas of the country since almost all the reported species come from the North Pacific; the diversity of ascidians from other parts of the country, especially the Caribbean, is still unknown.